Efficiency of Microfinance Institutions in India: Evidence from Malmquist Indices (International Research in Economics and Finance, 2017)
The current study constructs a balanced panel data set on microfinance institutions in India during 2008-2012 and employs a data envelopment analysis to examine the efficiency of the institutions. The results show a decrease of 0.3 per cent in productivity during the study period. In addition, the technical efficiency change, pure efficiency change and scale efficiency attributes to the overall inefficiency of the institutions. Also, profit institutions are more efficient than non-profit institutions. Results from Tobit regressions indicate that the impact of population and GDP on the efficiency of the institutions is significant, but that of the number of microfinance institutions is not.